Nasoalveolar molding: Use of reverse expansion screw in retraction of cleft premaxilla in a case of bilateral cleft lip and palate - Neha; Tulika Tripathi; Priyank Rai; Padam Singh Bhandari (Wolters Kluwer Medknow Publications, 2015)
The projecting premaxilla in case of bilateral cleft lip and palate presents a great challenge to the surgical repair of the cleft lip due to difficulty in suturing the large defect. Furthermore, the short columella and nasal dysmorphology result in compromised esthetics even with repeated surgeries. The current case report describes the use of an expansion screw for retraction of cleft premaxilla prior to surgical repair along with nasal molding in a 5-month-old infant.